The synergetic effect of hot rolling and heat treatment on mechanical properties: AISI-1045 and JIS-SUP 9 Steel - Owais, M. (ASTM International, 2020)
Hot rolling and heat treatment are the two industrial metallurgical applications used with compatible steels to modify mechanical properties. In this article, we studied the combined effect of hot rolling and heat treatment at constant parameters on medium carbon steels with respect to reduced thickness. For this purpose, the precasted round billets (110-mm diameter) of AISI-1045 and the square billet (110 by 110 mm) of JIS-SUP 9 were hot rolled and the thickness was reduced up to 6, 8, and 12 mm and 18, 28, and 45 mm, respectively. The hot rolled billets were subjected to heat treatment. The chemical compositions of the steels were evaluated by optical emission spectroscopy, whereas the microstructures of the samples after hot rolling and heat treatment were observed through metallography. Furthermore, the mechanical properties of the samples were calculated through the tensile test. The results showed a fall in ductility and toughness with respect to reduced thickness and a rise in mechanical strength. It is noteworthy that breaking strength remained unaffected. The JIS-SUP 9 steel is a spring steel, which is the reason for its better mechanical properties (e.g., toughness and ductility) as compared with AISI-1045 steel. Â© 2019 by ASTM International, 100 Barr Harbor Drive, PO Box C700, West Conshohocken, PA 19428-2959.